Pengaruh Kompetensi Profesional Guru, Motivasi Siswa, dan Fasilitas Belajar terhadap Hasil Pembelajaran Pendidikan Agama Kristen Pada Masa Pandemi Covid-19 - Zarah D. Bureni; Hendrik A.E Lao (Sekolah Tinggi Teologi Real Batam, 2022)
This study aims to determine the effect of teacher professional competence, student motivation, and learning facilities on the learning outcomes of Christian religious education. The type of research used is survey research with a quantitative approach. Data was collected by using questionnaire, observation, and documentation methods. The results of the study are as follows: First, the t-table ANOVA test results in a joint effect of teacher professional competence, student motivation, and learning facilities on the learning outcomes of Christian religious education by 40.1 percent. Second, the coefficients table test for teacher professional competence obtained t_count of 2,335 more than t_table 2.056 and a significant value of 0.028 less than 0.05 for student motivation, t-count 2.097 more than t_table 2.056 and a significant value of 0.046 less than 0.05 so that the results have a significant effect. partial variables of teacher professional competence and student motivation on learning outcomes of Christian religious education, while for learning facilities t_count minus 1754 is less than t table 2,056 and a significant value of 0.091 more than 0.05 there is no partial effect of learning facilities on learning outcomes of Christian religious education. Thus, the variables of teacher professional competence and student motivation affect the learning outcomes of Christian religious education.Keywords: learning facilities; learning outcomes; teacher's professional competence; student motivation AbstrakPenelitian ini bertujuan untuk mengetahui pengaruh kompetensi profesional guru, motivasi siswa, dan fasilitas belajar terhadap hasil pembelajaran pendidikan agama Kristen. Jenis penelitian yang digunakan adalah penelitian survei dengan pendekatan kuantitatif. Pengumpulan data dilakukan dengan metode angket, observasi, dan dokumentasi. Hasil penelitian sebagai berikut: Pertama, Uji t tabel ANOVA hasilnya terdapat pengaruh secara bersama-sama kompetensi profesional guru, motivasi siswa, dan fasilitas belajar terhadap hasil belajar pendidikan agama Kristen sebesar 40,1 persen. Kedua, Uji tabel coefficients untuk kompetensi profesional guru diperoleh t_hitung sebesar 2.335 lebih dari t_tabel 2.056 dan nilai Signifikan 0,028 kurang dari 0,05 untuk motivasi siswa t hitung 2.097 lebih dari t_tabel 2.056 dan nilai signifikan 0,046 kurang dari 0,05 sehingga hasilnya terdapat pengaruh secara parsial variabel kompetensi profesional guru dan motivasi siswa terhadap hasil belajar pendidikan agama Kristen, sedangkan untuk fasilitas belajar t_hitung minus 1754 kurang dari t tabel 2.056 dan nilai signifikan 0,091 lebih dari 0,05 tidak ada pengaruh secara parsial fasilitas belajar terhadap hasil belajar pendidikan agama Kristen. Dengan demikian, variabel kompetensi profesional guru dan motivasi siswa berpengaruh terhadap hasil belajar pendidikan agama Kristen.Kata kunci: fasilitas belajar; hasil belajar; kompetensi profesional guru; motivasi siswa